Procedures between training and reactivation influence the destabilization of instrumental sucrose memory - Cheng, Chaoran; Exton-McGuinness, Marc T. J.; Lee, Jonathan L. C. (Frontiers in Behavioral Neuroscience, 2022)
Memory destabilization and reconsolidation is hypothesized to be a fundamental mnemonic process that can underpin memory updating. Instrumental memories have been shown recently to be destabilized following a reactivation session that involves a change in instrumental reward contingency. However, the acquisition and performance of an instrumental response occurs in the presence of the learning of other reward-related memories. This may influence the ability of a given reactivation session to destabilize the previously-learned instrumental memory. Here we present a series of experiments in male rats involving an instrumental memory trained on an FR1 schedule over 10 days, and then reactivated in a session that imposed a VR5 schedule of reinforcement. When MK-801 was injected prior to the VR5 reactivation session, it reliably impaired subsequent instrumental performance at test only when the reactivation session occurred 48 hr, and not 24 hr, after the end of training. The interposition between the end of training and the reactivation session of a context extinction session, an additional VR5 reactivation session, or indeed the simple experience of being handled and injected with vehicle, resulted in MK-801 no longer having an amnestic effect on test performance. While we do not have a clear account for the process and mechanism underpinning this apparent selectivity of effect of the VR5 session to destabilize the instrumental memory, it does additionally highlight the need for greater understanding of the conditions that facilitate reactivation-induced memory destabilization.